A Bridge Too Far? Challenges in Evaluating Principal Effectiveness. (August 2014) - Fuller, Edward J.; Hollingworth, Liz
Purpose: The purpose of this article is to examine the assumptions underlying efforts to evaluate principal effectiveness in terms of student test scores, to review extant research on efforts to estimate principal effectiveness, and to discuss the appropriateness of including estimates of principal effectiveness in evaluations of principals.Method: We review 10 different strategies for estimating principal effectiveness based on student test scores, representing all of the strategies currently employed by states and districts. We base our reviews on the literature in three areas: use of test scores, evaluation, and statistical approaches to estimating the effects of individuals and schools on student test scores.Conclusions: We conclude there are currently no strategies to estimate principal effectiveness that accurately capture the independent effect of principals on student test scores; thus, these current strategies send inaccurate signals to both principals and those who make employment decisions about principals. Moreover, we also conclude a substantial proportion of principals could not be included in the most accurate strategies to assess principal effectiveness.Implications: This research has profound implications for states and districts implementing principal evaluation systems, particularly those making high-stakes decisions about principals based on statistical estimates of principal effectiveness. Indeed, such statistical estimates should be used not for making judgments or decisions about principals but rather as a screening tool to identify where states and districts should focus more in-depth and accurate strategies to evaluate principal effectiveness.